Land use policy and green utilization efficiency in border cities: evidence from northeastern China’s carbon reduction practice - Fan, Xuncheng; Zhao, Lili (Frontiers in Environmental Science, 2025)
IntroductionEfficient land resource utilization is increasingly important for regional development as global attention focuses on sustainable development in border regions. This study develops an innovative ’border location‐functional differentiation‐efficiency coupling‘ theoretical framework.MethodsUsing this foundation, we employ regression‐based path analysis and spatial analytical methods to evaluate the relationship between land use policies and green utilization efficiency across fourteen northeastern China border cities from 2010 to 2020.ResultsOur research reveals significant spatial heterogeneity in land use patterns. Industrial cities show lower land green utilization efficiency (8.14‐12.48 tons CO2/10,000 yuan). In contrast, port cities maintain higher utilization efficiency (average 1.54 tons CO2/10,000 yuan). Land use policies oriented toward industrial transformation and ecological protection significantly enhance land green utilization efficiency. Energy intensity (−6452.09, p < 0.05) and industrial structure (−4664.92, p < 0.01) are key inhibiting factors. Different types of cities present differentiated policy responses.DiscussionIndustrial cities promote technological upgrades through digital transformation. Ecological cities emphasize protection-oriented smart development. These findings enrich theoretical research on land use efficiency in border regions. They also provide a scientific basis for formulating differentiated land use policies. This has important practical significance for promoting ecological civilization construction and high-quality development in China’s northern border regions.